2023
DOI: 10.1186/s12872-023-03459-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C may reduce troponin and CKMB levels after PCI and CABG: a meta-analysis

Sander Rozemeijer,
Harri Hemilä,
Marlinde van Baaren
et al.

Abstract: Background Ischemia/reperfusion injury contributes to periprocedural myocardial injury (PMI) in patients undergoing percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG). PMI can be estimated by the elevation of troponin (Tn) and creatine kinase-MB (CKMB) plasma levels, and it is associated with increased risk of cardiovascular events and mortality. Vitamin C might have a beneficial effect on PMI by improving endothelial function, improving myocardial perfusion, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Our study focuses on PH, but vitamin C appears to have other cardiac effects. Meta-analyses indicate that vitamin C can lower systemic blood pressure [ 162 ], increase low levels of LVEF [ 130 ], decrease the risk of AF in high-risk populations [ 129 ], decrease troponin levels in cardiac stress [ 163 ], and improve endothelial function [ 164 ]. One RCT found that vitamin C prevented postangioplasty restenosis [ 165 ], and another that vitamin C prevented myocardial injury after elective PCI [ 166 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study focuses on PH, but vitamin C appears to have other cardiac effects. Meta-analyses indicate that vitamin C can lower systemic blood pressure [ 162 ], increase low levels of LVEF [ 130 ], decrease the risk of AF in high-risk populations [ 129 ], decrease troponin levels in cardiac stress [ 163 ], and improve endothelial function [ 164 ]. One RCT found that vitamin C prevented postangioplasty restenosis [ 165 ], and another that vitamin C prevented myocardial injury after elective PCI [ 166 ].…”
Section: Discussionmentioning
confidence: 99%